2004
DOI: 10.1021/ja0488028
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Binds Cu2+ in a Mononuclear Metal Ion Binding Site

Abstract: Amyloid-beta (Abeta) peptide is the principal constituent of plaques associated with Alzheimer's disease and is thought to be responsible for the neurotoxicity associated with the disease. Metal ions have been hypothesized to play a role in the formation and neurotoxicity of aggregates associated with Alzheimer's disease (Bush, A. I.; et al. Proc. Natl. Acad. Sci. U.S.A. 2003, 100, 11934). Elucidation of the chemistry through which transition-metal ions participate in the assembly and toxicity of Abeta oligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
241
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(265 citation statements)
references
References 37 publications
23
241
1
Order By: Relevance
“…These results are concordant with those obtained previously on working with individual metal ions [29][30][31][32]. Although blood and internal biochemical environment is characterized by a…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are concordant with those obtained previously on working with individual metal ions [29][30][31][32]. Although blood and internal biochemical environment is characterized by a…”
Section: Discussionsupporting
confidence: 92%
“…Several spectroscopic studies have indicated that the copper-binding site of Aβ consists of the three histidine residues His6, His13 and His14 and an as yet undefined fourth ligand; proposed ligands include Tyr10 [19,[38][39][40], the Nterminal nitrogen [30] or an as yet unidentified carboxylate side chain [31,32].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…1B, blue squares) contained copper in a 1:1 stoichiometry. This is compatible with the notion that A␤ 1-40 has one high affinity Cu(II)-binding site (33,39) and that Cu(II) is bound to the aggregates in a 1:1 ratio (32,44). In addition, ICP-MS data showed that the copper stays bound to the aggregates during the entire time course of the experiment (72 h).…”
Section: Cu(ii):a␤ 1-40 Ratiosupporting
confidence: 86%
“…An intriguing approach for elucidating the complex role of Cu(II) in the A␤ aggregation mechanism would be the use of complementary kinetic methods as advocated in a recent review (31). In particular, kinetic studies on Cu(II) bound to A␤ have been lacking, and to our knowledge only end point determination of the copper content in the amyloid aggregates has been performed (32,33). Nevertheless, this information is as important as the out-come of studies on the peptide disappearance or aggregation formation kinetics for elucidating the A␤-Cu(II) interplay and will form the basis for studies of neuro-cytotoxicity under defined metallopeptide conditions.…”
mentioning
confidence: 99%
“…The identity of the fourth ligand includes tyrosine at position 10 (Tyr10) (16,(19)(20)(21), the N-terminal nitrogen (22), or an undefined carboxylate side chain (23). Our EPR studies indicate that increasing the Cu 2+ above ∼0.3 mol/mol peptide-induced line broadening in the Cu 2+ EPR spectra suggests the presence of dipolar or exchange effects (17,19).…”
mentioning
confidence: 82%